2021
DOI: 10.3389/fpsyt.2021.640795
|View full text |Cite
|
Sign up to set email alerts
|

Text4Support Mobile-Based Programming for Individuals Accessing Addictions and Mental Health Services—Retroactive Program Analysis at Baseline, 12 Weeks, and 6 Months

Abstract: Objective: Where traditional approaches fall short, widely accessible and accepted, yet under leveraged, digital technologies such as text messaging present novel opportunities to solve a range of health care solutions. The following provides a preliminary analysis of the Text4Support program, a text-messaging intervention using the principles of cognitive behavioral therapy, which seeks to support the health and well-being of individuals seeking support for addiction or mental health concerns. The goal of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 70 publications
3
29
1
Order By: Relevance
“…As such, during recessions, governments typically lay off staff, do not replace retiring staff, or avoid creating new heavily human resource intensive mental health services [ 137 , 138 ]. Therefore, health policy and practice implications should also consider the adoption of low cost, evidence-based interventions such as bibliotherapy, Internet-Delivered Cognitive Behavioural Therapy, supportive text messaging, and encouragement of community and family level emotional support [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. Research evidence has suggested that support from family and friends is protective during natural disasters and two studies in this review suggest that positive social support provides additional protection against anxiety and depression during times of economic recession [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, during recessions, governments typically lay off staff, do not replace retiring staff, or avoid creating new heavily human resource intensive mental health services [ 137 , 138 ]. Therefore, health policy and practice implications should also consider the adoption of low cost, evidence-based interventions such as bibliotherapy, Internet-Delivered Cognitive Behavioural Therapy, supportive text messaging, and encouragement of community and family level emotional support [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. Research evidence has suggested that support from family and friends is protective during natural disasters and two studies in this review suggest that positive social support provides additional protection against anxiety and depression during times of economic recession [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected between August 2019 and February 2020. The instrument was not validated but was adopted from surveys used in previous text messaging programs [ 2 , 3 , 19 ]. Participants entered their mobile phone numbers as their unique study ID number, which prevented multiple participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A recent evaluation of Text4Support indicates that the program is effective and accepted by individuals seeking access to outpatient mental health services in the Edmonton Zone. A large proportion of these subscribers reported always or often reading of the messages (25/26, 96%), and after receiving the service for 6 months, the majority agreed that the text messages (TxMs) were to the point (18/24, 75%), supportive (22/24, 92%), and positive (22/24, 92%) [ 19 ]. In a similar study, the authors reported higher satisfaction with the texting service among female participants, who reported an improvement in coping with different stresses related to the COVID-19 pandemic along with an improvement in their quality of life, compared with their male counterparts [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to explore and compare the impact of accessible and rapidly implementable mental health interventions such as supportive text messages on school board staff and other employees. Interventions such as supportive and informative text messaging can be used to alleviate the long-term mental health effects of the wildfires, floods, and the COVID-19 pandemic [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Future studies may also examine the contribution of adverse childhood experiences and personal traumas such as bereavement, domestic violence, and sexual trauma on mental health outcomes in a community affected by multiple natural disasters.…”
Section: Discussionmentioning
confidence: 99%